An antimicrobial molecule mitigates signs of sepsis in vivo and eradicates infections from lung tissue. Issue 1 (20th November 2019) - Quercini, Leila; Brunetti, Jlenia; Riolo, Giulia; Bindi, Stefano; Scali, Silvia; Lampronti, Ilaria; D'Aversa, Elisabetta; Wronski, Sabine; Pollini, Simona; Gentile, Mariangela; Lupetti, Pietro; Rossolini, Gian Maria; et al.
Abstract: The peptide sequence KKIRVRLSA was synthesized in a dimeric structure (SET‐M33DIM) and evaluated as a candidate drug for infections due to multidrug‐resistant (MDR) Gram‐negative pathogens. SET‐M33DIM showed significant antibacterial activity against MDR strains of Klebsiella pneumoniae, Acinetobacter baumannii, and Escherichia coli (Minimal Inhibitory Concentration [MICs], 1.5‐11 µM), and less activity against Pseudomonas aeruginosa (MICs, 11‐22 µM). It showed very low toxicity in vitro, ex vivo, and in vivo; in cytotoxicity tests, its EC50 was as much as 22 times better than that of SET‐M33, a peptide with the same amino‐acid sequence, but synthesized in tetra‐branched form (638 vs 28 µM). In in vivo and ex vivo experiments, SET‐M33DIM cleared P. aeruginosa infection, significantly reducing signs of sepsis in animals, and restoring cell viability in lung tissue after bacterial challenge. It also quelled inflammation triggered by LPS and live bacterial cells, inhibiting expression of inflammatory mediators in lung tissue, cultured macrophages, and bronchial cells from a cystic fibrosis patient.